Guidelines for the use and reporting of Artificial Intelligence in scientific-academic journals: English translation - Penabad-Camacho, Liana (2024)
Introduction. Artificial Intelligence (AI) proposes a restructured approach to the traditional methods of conducting and publishing scientific research since it provides tools that complement, re-learn, and simplify complex processes typically associated with human-driven research. The diversity of mechanisms AI provides requires transparent reporting of its use and the guarantee that they are consistent with the rigorous scientific communication and its editorial management ecosystem (comprised of editors, reviewers, and authors). Objective. This document aims to provide guidelines for reporting the use of AI in activities related to the scientific publication process. The three roles mentioned above are equipped with concepts, principles, and recommendations that offer literacy and learning mechanisms for those individuals involved in activities related to knowledge communication. Guidelines. The guidelines are divided into four sections. The first section includes the concepts necessary to understand the dynamics proposed in the principles and recommendations. Notably, the definition of prompts (primary, second, and supplemental), the prompt net, and the diagrams conceptualizing their use are proposed. The second section covers editors and editorial teams and includes recommendations for implementing AI-related policies in their journals. The third section gives reviewers good practices for using AI to evaluate a scientific communication unit. The fourth section offers authors an ethical framework and concrete tools to use AI in their work and report it in their manuscripts. Final reflection: The ultimate goal for using AI must be the common good and the improvement of people’s quality of life. An ethical exercise minimizing the introduction of bias or misinformation should be a backbone for using this tool. Future updates of these guidelines must never forget that this is an evolving phenomenon.